Concurrent infection of bluetongue and peste-des-petits-ruminants virus in small ruminants in Haryana State of India - Maan, Sushila; Kumar, Aman; Gupta, Akhil Kumar; Dalal, Anita; Chaudhary, Deepika; Gupta, Tarun Kumar; Bansal, Nitish; Kumar, Vinjay; Batra, Kanisht; Sindhu, Neelesh; Kumar, Ankit; Mahajan, Nand K.; et al. (Wiley, 2018)
Bluetongue (BT) and peste-des-petits-ruminants (PPR) are major transboundary diseases of small ruminant, which are endemic in India. Testing of bluetongue virus (BTV) and peste-des-petits-ruminants virus (PPRV) from recent outbreaks (2015–2016) in different regions of Haryana State of India revealed that 27.5% of the samples showed the presence of dual infection of BTV and PPRV. Analysis of Seg-2 of BTV (the serotype-determining protein) showed the presence of BTV-12w in several isolates. However, analysis of N gene fragment amplicons showed that viruses belong to lineage IV were most closely related to a pathogenic strain of PPRV from Delhi. This is the first report of co-circulation of PPRV lineage IV and bluetongue virus serotype 12 in the state.